2006
DOI: 10.1002/mnfr.200500171
|View full text |Cite
|
Sign up to set email alerts
|

Predicting heat inactivation of Staphylococcus aureus under nonisothermal treatments at different pH

Abstract: The aim was to assess whether heat resistance data obtained from isothermal treatments allow the estimation of survivors of Staphylococcus aureus under nonisothermal conditions and to find a model that accurately predicts its heat inactivation at constantly rising heating rates (0.5-9 degrees C/min) in media of different pH (4.0-7.4). S. aureus showed a higher heat resistance under isothermal treatments at pH 4.0 than at pH 5.5-7.4. However, under nonisothermal treatments S. aureus increased its heat resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…4a). Previous results from different authors have shown that nonisothermal heating influences the heat resistance of vegetative bacteria (Stephens et al 1994;Hassani et al 2006), probably through the induction of heat shock protein (HSP) formation (Periago et al 2002), which can be induced very rapidly (Yura et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…4a). Previous results from different authors have shown that nonisothermal heating influences the heat resistance of vegetative bacteria (Stephens et al 1994;Hassani et al 2006), probably through the induction of heat shock protein (HSP) formation (Periago et al 2002), which can be induced very rapidly (Yura et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…7 and 8, respectively. The original authors of the data are Hassani et al (8,9,10), who also reported the organism's isothermal survival patterns at these two pH levels (10). As before, the WeLL model's parameters were calculated using data obtained at clearly lethal temperatures, i.e., in the range of 54 to 62°C.…”
Section: When the Newly Defined Rate Parameter In The Form Of B[t(t)mentioning
confidence: 99%
“…Its cells can produce "heat shock proteins," which help them to survive mild heat treatments (1,11). Other organisms, Salmonella enterica and Bacillus cereus among them, can also develop defensive mechanisms that help them to survive in an acidic environment (8,9,13). Whether adaptation allows the cells to avoid injury or to repair damage once it has occurred, or both, should not concern us here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms reveal stress adaptation, i.e., the increase of resistance to environmental conditions that would normally be lethal (e.g., heat, acidity and chemical agents), by pre-exposure to a similar stress factor (Cebrian et al, 2009;Hassani et al, 2005Hassani et al, ,2006Juneja and Marks, 2005;Valdramidis et al, 2006Valdramidis et al, ,2007 or a different kind of stress (Leyer and Johnson, 1993;Juneja and Novak, 2003;Skandamis et al, 2008Skandamis et al, ,2009. The ability of a stress-adapted microorganism to resist when exposed to another kind of environmental stress is known as cross protection (Juneja and Novak, 2003).…”
Section: Introductionmentioning
confidence: 99%